2020
DOI: 10.1007/s10639-020-10319-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of technostress on academic productivity of university students

Abstract: There has been increasing interest among researchers to understand the negative effects of technology, in the last two decades. Technostress or stress induced due to technology is extensively reported in the literature, among working professionals. Even though there has been an increased proliferation of digital devices in academia, there is a dearth of studies examining the prevalence of technostress and its impact among students. This study examines the prevalence of technostress among the younger population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 49 publications
13
111
2
8
Order By: Relevance
“…Notwithstanding, ICTs come with benefits for students demonstrated via performance improvements, saving institutional resources and time, high student satisfaction [13,14], convenience, flexibility, and extended access to quality learning support [15]. ICT allows universities to streamline institutional management, increase openness, and accelerate students' academic data processing [16,17]. These benefits are said to advance the learning and teaching process [18].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, ICTs come with benefits for students demonstrated via performance improvements, saving institutional resources and time, high student satisfaction [13,14], convenience, flexibility, and extended access to quality learning support [15]. ICT allows universities to streamline institutional management, increase openness, and accelerate students' academic data processing [16,17]. These benefits are said to advance the learning and teaching process [18].…”
Section: Introductionmentioning
confidence: 99%
“…From these limitations, it is suggested that subsequent studies include eLearning as the factors that prohibit technostress and expand investigations to see whether the "online" elements in eLearning could bring any differences in technostress level. Future researchers could look at whether learning a technical skill online help to reduce technostress as proven by previous studies (Chiappetta, 2017;Joo et al, 2016;La Torre et al, 2019;Upadhyaya & Vrinda, 2021) or spiking anxiety higher and make technostress worsen. Furthermore, a longitudinal study could be conducted to see the frequency of training and technical support an employee needs to reduce their technostress.…”
Section: Conclusion and Recommendationmentioning
confidence: 97%
“…Technostress prohibitors also can be known as coping behaviour (Tarafdar et al, 2019) which refers to an organisational mechanism that reduces stress and anxiety among employees towards technology (Ragu-Nathan et al, 2008). Three major components in si+++tuational prohibitor could be coping strategies towards technostress creator; literacy facilitation (Ragu-Nathan et al, 2008), technical support (Bondanini et al, 2020;Joo et al, 2016;Li & Wang, 2021;Ragu-Nathan et al, 2008) and training (Joo et al, 2016;La Torre et al, 2020;Upadhyaya & Vrinda, 2021).…”
Section: Technostress Prohibitorsmentioning
confidence: 99%
See 2 more Smart Citations